What is the meaning of some of the marks incised in the back of Old panel paintings? - Melo, Helena P. (2018)
A bibliographic survey of incised marks of a rough appearance, creating straight parallel or intersecting lines, found on the back of Portuguese oak panel paintings is presented. Although Portuguese literature on this matter mostly suggests that these marks are related to the quality of the wood or to a panelmaker’s workshop, the fact that most of them do not proceed between adjacent boards, indicates that they were made prior to panel construction. Since they appear exclusively on Baltic oak and on cleaved untreated surfaces, they must be connected to oak wood cutting, exploitation and trade, notably in the Baltic region, as suggested by J-A. Glatigny and M. Rief, and are not marks related to the manufacture of the panels as they have been previously considered